ANALYSIS OF TENSILE STRENGTH AND EFFORTLESSNESS OF BIODEGRADABLE PLASTIC WITH THE ADDITION OF TiO2 - Yurdanianti, Fira; Jumardin, Jumardin (SAINFIS: Jurnal Sains Fisika, 2024)
Biodegradable plastic (bioplastic) is a very potential candidate because it is generally biodegradable. Starch-based bioplastics have several advantages, including renewable, biodegradable and easy to process. The aim of this research is to determine the potential of durian seed waste starch with the addition of TiO2 as an environmentally friendly bioplastic. The method used is by measuring thickness, tensile strength testing and creep strength testing. This research resulted in the best material being obtained in samples with a thickness of 0.2 mm, a tensile strength of 22.96 % and an elongation strength of 25.55 %. The results obtained are biodegradable plastic made from Durian seed waste starch with the addition of TiO2 which can be an alternative to plastic. The basic waste materials of course the results obtained in this research are environmentally friendly, safe for health and of course have affordable prices for all levels of society.